Diaphragm and battery, electrochemical device and electronic equipment comprising the same

CN123018357APending Publication Date: 2026-10-30HUIZHOU LIWINON ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611296868.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

因此,提供一种兼具电解液浸润性与循环稳定性的协同优化隔膜,进而提高锂电池在大规模储能应用中的本质安全性,对于有效解决目前存在的锂电池因热失控导致的安全问题具有重要的意义

Benefits of technology

[0021]本申请至少具有以下有益效果:本申请提供的隔膜,在基膜上设置了复合涂层,复合涂层包括无机涂层和有机涂层,并将复合涂层中的有机涂层设置为大颗粒(第一有机物颗粒)、小颗粒(第二有机物颗粒)混合。有机涂层中,大颗粒与小颗粒的混合形成了梯度孔隙结构——大颗粒间形成宏观孔隙,小颗粒填充微观间隙。在电池组装(如卷绕或叠片)及后续充放电过程中的体积膨胀收缩时,具有一定压缩性的大颗粒能够发生适形形变。这种形变会动态微调大颗粒之间的距离a,避免了因刚性接触导致的基膜拉伸变薄,从而提升安全性的同时不牺牲孔隙率。与此同时,由于小颗粒的存在及其与大颗粒的距离b控制,当大颗粒受压形变时,小颗粒能够在大颗粒间隙中起到支撑和分散应力的作用,防止涂层因过度压实而完全塌陷(即防止b值归零占比过高)。这使得涂层在受压后仍能保持设计的微观通道,确保了长期循环过程中的离子电导率稳定性。最终,本申请提供的电池隔膜,通过多尺度孔隙构筑和压缩性动态调节,实现了电解液浸润性与循环稳定性的协同优化,可适配电动汽车和电网规模的电能存储等大容量应用,满足大容量、高循环稳定性的要求,可广泛应用于新能源领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_7
    Figure SMS_7
Patent Text Reader

Abstract

The application discloses a diaphragm and an electric core, an electrochemical device and an electronic device comprising the same. The diaphragm provided by the application is provided with a composite coating on a base film, and the organic coating in the composite coating is provided as a mixture of large and small particles, macro-pores are formed between the large particles, and the small particles fill micro-gaps. This structure not only ensures the rapid penetration of electrolyte (through the large-particle pores), but also increases the capillary effect through the small particles, promotes the uniform distribution of electrolyte in the diaphragm, and thus reduces the interface impedance. Moreover, the large particles are compressible and can be dynamically adjusted: the large particles are deformed under pressure during battery assembly or charging and discharging, temporarily increasing the local porosity and promoting electrolyte infiltration; after the pressure is released, partial rebound can maintain the structural stability and avoid the decrease in wettability caused by pore collapse. Ultimately, the battery diaphragm realizes the synergistic optimization of electrolyte wettability and cycle stability through multi-scale pore construction and compressive dynamic adjustment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electrochemical energy storage technology, and in particular to diaphragms and cells, electrochemical devices and electronic devices containing them. Background Technology

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their numerous advantages, including high energy density, good rate performance, low self-discharge rate, and environmental friendliness. As high-energy-density lithium-ion batteries are increasingly developed and applied in large-capacity applications, their safety has become increasingly important. Among these, thermal runaway has become a significant safety factor, with internal short circuits considered the primary cause. An internal short circuit causes a sudden increase in battery temperature, triggering numerous exothermic reactions, such as the reduction / oxidation decomposition of the organic electrolyte at the anode / cathode interface and the thermal decomposition of the cathode material. These reactions generate substantial heat and flammable gas products, causing a rapid increase in internal pressure and temperature within a short period, ultimately leading to thermal runaway and potentially resulting in battery rupture, fire, or even explosion.

[0003] Typically, such internal short circuits are caused by the shedding of electrode active particles or the breakage of the separator, especially when lithium batteries are subjected to mechanical or thermal shocks (such as vibration, impact, and overheating). Therefore, providing a synergistically optimized separator that combines electrolyte wettability and cycle stability to improve the inherent safety of lithium batteries in large-scale energy storage applications is of great significance for effectively solving the safety problems caused by thermal runaway in lithium batteries. Summary of the Invention

[0004] This application aims to address at least one of the technical problems existing in the prior art. To this end, this application proposes a separator and a battery cell, electrochemical device, and electronic device comprising the separator, aiming to solve the safety problems caused by thermal runaway in current lithium batteries.

[0005] A first aspect of this application provides a diaphragm, comprising a base membrane and a composite coating disposed on at least one side of the base membrane. The composite coating comprises an inorganic coating and a first organic coating, wherein the first organic coating is disposed on the surface of the inorganic coating away from the base membrane. The first organic coating comprises first organic particles and second organic particles, wherein the median particle size Dv50 of the first organic particles is greater than the median particle size Dv50 of the second organic particles. The inorganic coating comprises inorganic particles. In the first organic coating, the values ​​of the distance 'a' between the first organic particles, the distance 'b' between the first organic particles and the second organic particles, and the compressibility 'd' of the diaphragm satisfy the following relationship: ; Where a is in μm and b is in μm.

[0006] In some embodiments, the areal density α and thickness β of the inorganic coating satisfy the relationship: 0.1 < α / β ≤ 5, where the unit of α is g / m³. 2 The unit of β is μm.

[0007] In some embodiments, the composite coating is disposed on one side of the base film.

[0008] In some embodiments, the diaphragm further includes a second organic coating disposed on the surface of the base membrane away from the composite coating.

[0009] In some embodiments, the distance 'a' between the first organic particles satisfies the following condition: 0 ≤ a < 50 μm, and the percentage of a = 0 is < 50%.

[0010] In some embodiments, the distance b between the first organic particle and the second organic particle satisfies: 0 ≤ b < 25 μm, and the percentage of b = 0 is < 70%.

[0011] In some embodiments, the distance c between the second organic particle and the second organic particle satisfies: 0 ≤ c < 10 μm, and the proportion of c = 0 is < 90%.

[0012] In some embodiments, the median particle size Dv50 of the first organic particles is 3.8~11.0 μm, and the particle size distribution width is 0.98~5.88.

[0013] In some embodiments, the median particle size Dv50 of the second organic particles is 0.3~0.8 μm, and the particle size distribution width is 1.56~4.17.

[0014] In some embodiments, the inorganic particles have a median particle size Dv50 of 0.3~0.7 μm, a particle size distribution width of 2.8~6.5, and a specific surface area of ​​8~16 m². 2 / g.

[0015] In some embodiments, the diaphragm includes at least one of the following: (a1) The first organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (a2) The second organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (a3) The inorganic particles are selected from at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, silicon hydroxide, barium sulfate, zirconium oxide, calcium oxide, titanium dioxide, cerium dioxide, or apatite; (a4) The thickness D1 of the first organic coating ranges from 2.0 to 6.5 μm; (a5) The thickness β of the inorganic coating ranges from 0.2 to 2.5 μm; (a6) The compressibility d of the diaphragm satisfies: 0 < d < 100%.

[0016] In some embodiments, the composite coating is disposed on one side of the base membrane, and the membrane further includes a second organic coating disposed on the surface of the base membrane away from the composite coating, the second organic coating comprising third organic particles.

[0017] In some embodiments, the diaphragm includes at least one of the following: (b1) The thickness D2 of the second organic coating ranges from 0.3 to 1.0 μm; (b2) The distance f between the third organic particles satisfies: 0 ≤ f < 10 μm, and the percentage of f = 0 is < 100%; (b3) The third organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (b4) The median particle size Dv50 of the third organic particles is 0.3~0.8μm and the particle size distribution width is 1.56~4.17.

[0018] A second aspect of this application also provides a battery cell comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the separator described above.

[0019] A third aspect of this application also proposes an electrochemical device comprising the aforementioned battery cell.

[0020] A fourth aspect of this application also proposes an electronic device comprising the aforementioned electrochemical device.

[0021] This application has at least the following beneficial effects: The separator provided in this application has a composite coating on the base film. The composite coating includes an inorganic coating and an organic coating, and the organic coating in the composite coating is configured as a mixture of large particles (first organic particles) and small particles (second organic particles). In the organic coating, the mixture of large and small particles forms a gradient pore structure—macropores are formed between large particles, and small particles fill the micro gaps. During the volume expansion and contraction of the battery assembly (such as winding or stacking) and subsequent charging and discharging processes, the large particles with a certain degree of compressibility can undergo conformal deformation. This deformation dynamically fine-tunes the distance 'a' between the large particles, avoiding the base film from stretching and thinning due to rigid contact, thereby improving safety without sacrificing porosity. At the same time, due to the presence of small particles and the control of their distance 'b' from the large particles, when the large particles are deformed under pressure, the small particles can play a supporting and stress-dispersing role in the gaps between the large particles, preventing the coating from completely collapsing due to excessive compaction (i.e., preventing the proportion of b values ​​to be zero from being too high). This allows the coating to maintain its designed microchannels even under pressure, ensuring the stability of ionic conductivity during long-term cycling. Ultimately, the battery separator provided in this application achieves synergistic optimization of electrolyte wettability and cycle stability through multi-scale pore construction and dynamic adjustment of compressibility. It is suitable for large-capacity applications such as electric vehicles and grid-scale energy storage, meeting the requirements of high capacity and high cycle stability, and can be widely used in the new energy field. Attached Figure Description

[0022] The embodiments described in this application are not limited to the accompanying drawings, which are only some of the embodiments described herein. Those skilled in the art can obtain drawings of other embodiments based on the content of this application.

[0023] Figure 1 One schematic diagram of the diaphragm provided in this application; Figure 2 Another schematic diagram of the diaphragm provided in this application; Wherein: 1-base film; 2-composite coating; 3-second organic coating; 4-first organic coating; 4.1-first organic particles; 4.2-second organic particles; 5-inorganic coating. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application. The embodiments of this application may omit unnecessary detailed descriptions. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid making the following description unnecessarily lengthy and to facilitate understanding by those skilled in the art.

[0025] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0026] Additionally, quantities, ratios, and other numerical values ​​are sometimes presented in range format in this document. It should be understood that such range format is for convenience and brevity and should be interpreted flexibly to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or subranges covered within the range, as if each numerical value and subrange were explicitly specified.

[0027] In the detailed description and claims, a list of items connected by the terms "one of," "among," "a kind of," or other similar terms may mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.

[0028] In the detailed description and claims, the list of items connected by the term "at least one of" can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C.

[0029] In the following description, all figures disclosed in this application are approximations.

[0030] Throughout this specification, references to "implementation," "partial implementation," "one implementation," "another implementation," "specific method," or "partial method" mean that at least one implementation or embodiment in this application includes the specific features, structures, materials, or characteristics described in that implementation or embodiment.

[0031] In this application, numerical ranges are involved. Unless otherwise specified, the numerical ranges mentioned above are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Any lower limit can be combined with any upper limit to form a range not explicitly stated; and any lower limit can be combined with other lower limits to form a range not explicitly stated, just as any upper limit can be combined with any other upper limit to form a range not explicitly stated. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form a range not explicitly stated.

[0032] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limiting the invention, and that changes, substitutions and modifications can be made to the embodiments without departing from the spirit, principles and scope of the invention.

[0033] The term "polymer" refers to a polymeric compound prepared by polymerizing the same or different types of monomers. The general term "polymer" includes the terms "homopolymer," "copolymer," "trimer," and "interpolymer."

[0034] The term "coating" refers to one or more layers applied to one or both sides of a porous substrate material. Functional coatings comprise a mixture of at least one organic binder and at least one inorganic filler. In addition to the organic binder and inorganic filler, the protective porous layer may also include one or more additives. Functional coatings can be single-layer, double-layer, or multi-layer structures.

[0035] The term "binder" refers to a substance used to bond inorganic fillers to or to each other in a porous substrate material. Any organic binder that can bond inorganic fillers to or to each other in a porous substrate material may be used herein. Some non-limiting examples of organic binders include polyesters, polyamides, polyacrylic acid, polyethers, polyimides, polyolefins, rubbers, styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, cellulose, cellulose derivatives, latexes, and combinations thereof.

[0036] Solids and liquids: In the context of this application, unless otherwise defined, the terms “solid” and “liquid” shall be understood as solids and liquids under standard temperature and pressure conditions as defined by IUPAC. Herein, boiling point and melting point shall be understood as boiling point and melting point at standard atmospheric pressure, i.e., at 101325 Pa.

[0037] Positive electrode active material: As used herein and in the claims, the term "positive electrode active material" (also known as cathode active material) is defined as a material that is electrochemically active in a positive electrode or cathode. Active material should be understood as a material capable of capturing and releasing Li and / or Na ions when subjected to voltage changes over a predetermined time period.

[0038] <Septum> A first aspect of this application proposes a diaphragm, comprising a base membrane and a composite coating disposed on at least one side of the base membrane. The composite coating comprises an inorganic coating and a first organic coating, the first organic coating being disposed on the surface of the inorganic coating away from the base membrane. The first organic coating comprises first organic particles and second organic particles, the median particle size Dv50 of the first organic particles being greater than the median particle size Dv50 of the second organic particles. The inorganic coating comprises inorganic particles. In the first organic coating, the values ​​of the distance 'a' between the first organic particles, the distance 'b' between the first organic particles and the second organic particles, and the compressibility 'd' of the diaphragm satisfy the following relationship: ; Where a is in μm and b is in μm.

[0039] The separator according to the embodiments of this application has at least the following beneficial effects: The separator provided in this application has a composite coating on the base film. The composite coating includes an inorganic coating and an organic coating, and the organic coating in the composite coating is configured as a mixture of large particles (first organic particles) and small particles (second organic particles). In the organic coating, the mixture of large and small particles forms a gradient pore structure—macropores are formed between large particles, and small particles fill the micro gaps. During the volume expansion and contraction of the battery assembly (such as winding or stacking) and subsequent charging and discharging processes, the large particles with a certain degree of compressibility can undergo conformal deformation. This deformation dynamically fine-tunes the distance 'a' between the large particles, avoiding the base film from being stretched and thinned due to rigid contact, thereby improving safety without sacrificing porosity. At the same time, due to the presence of small particles and the control of their distance 'b' from the large particles, when the large particles are deformed under pressure, the small particles can play a supporting and stress-dispersing role in the gaps between the large particles, preventing the coating from completely collapsing due to excessive compaction (i.e., preventing the proportion of b values ​​to be zero from being too high). This allows the coating to maintain its designed microchannels even under pressure, ensuring the stability of ionic conductivity during long-term cycling. Ultimately, the battery separator provided in this application achieves synergistic optimization of electrolyte wettability and cycle stability through multi-scale pore construction and dynamic adjustment of compressibility. It is suitable for large-capacity applications such as electric vehicles and grid-scale energy storage, meeting the requirements of high capacity and high cycle stability, and can be widely used in the new energy field.

[0040] In some embodiments, the particle size Dv90 of the first organic particle is greater than the particle size Dv90 of the second organic particle.

[0041] In some embodiments, the particle size Dv10 of the first organic particle is larger than the particle size Dv10 of the second organic particle.

[0042] The first organic coating provided in this application is a mixed coating composed of large organic particles and small organic particles. The particle sizes Dv90, Dv50, and Dv10 of the first organic particles (large organic particles) are larger than the particle sizes Dv90, Dv50, and Dv10 of the second organic particles (small organic particles), respectively.

[0043] In some embodiments, the distance 'a' between the first organic particles satisfies the following condition: 0 ≤ a < 50 μm, and the percentage of a = 0 is < 50%. For example, 'a' can be 0 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or within any two of the above values. The percentage of a = 0 can be 10%, 20%, 30%, 40%, 49%, or within any two of the above values. If 'a' is too small and its percentage is too large, the large particles will be too densely packed, affecting the compressibility of the coating; if 'a' is too large, the diaphragm and electrode cannot maintain tight interfacial contact, leading to capacity decay during cycling due to poor contact.

[0044] In some embodiments, the distance *b* between the first organic particle and the second organic particle satisfies the following condition: 0 ≤ b < 25 μm, and the percentage of b = 0 is < 70%. For example, b can be 0 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, or fall within any two of the above values. The percentage of b = 0 can be 10%, 20%, 30%, 40%, 50%, 60%, 69%, or fall within any two of the above values. If b is too small and its percentage is too large, the distance between the large and small particles is too small, resulting in stress concentration between the diaphragm and the electrode, which cannot maintain tight interfacial contact, leading to capacity decay during cycling due to poor contact. If b is too large, the coating amount is too low, affecting the adhesion between the diaphragm and the electrode.

[0045] In some embodiments, the distance *c* between the second organic particles and the second organic particles satisfies the following condition: 0 ≤ *c* < 10 μm, and the percentage of *c* = 0 is < 90%. For example, *c* can be 0 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or within any two of the above values. The percentage of *c* = 0 can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, or within any two of the above values. If *c* is too small and its percentage is too large, the small particles will accumulate too high, and the excessive adhesion between the small particles will hinder electrolyte transport; if *c* is too large, the capillary effect will be weak, reducing the adhesion between the diaphragm and the electrode, which may lead to electrolyte bridging during cycling.

[0046] In some implementations, the proportions of a=0, b=0, and c=0 satisfy (proportion of a=0) < (proportion of b=0) < (proportion of c=0). The distance 'a' between large organic particles satisfies 0 ≤ a < 50 μm, and the proportion of a=0 is < 50%. The large organic particles constitute the main framework of the coating, ensuring that most of the large particles maintain micron-level gaps, preventing excessive aggregation of large particles from blocking the large ion transport channels within the coating. The distance 'b' between large and small organic particles satisfies 0 ≤ b < 25 μm, and the proportion of b=0 is < 70%. The small organic particles are dispersed in the gaps between the large particles, ensuring that a sufficient number of small particles exist independently in the gaps, acting as a bridge connecting the large particles and the bonding substrate. At a more microscopic scale, the distance c between small particles satisfies 0 ≤ c < 10 μm, and the proportion of c = 0 is < 90%. This allows small particles to contact or agglomerate in a large proportion, thereby forming a continuous or discontinuous ultrafine particle network on the surface and gaps of the macroscopic skeleton, which can improve the uniformity of the coating and the adhesion and coverage of the base film.

[0047] In some implementations, the compressibility d of the diaphragm satisfies: 0 < d < 100%.

[0048] In some embodiments, the overall compressibility d of the diaphragm includes: the compressibility d1 of the first organic particles and the compressibility d2 of the inorganic particles, wherein 0 < d < 100%, 1% ≤ d1 ≤ 99%, and 0 < d2 < 1%. The compressibility of the base membrane has a negligible effect on the overall compressibility of the diaphragm. The compressibility d1 of the first organic particles (large organic particles) satisfies: 1% ≤ d1 ≤ 99%. Exemplarily, d1 can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 99%, or within any two of the above values. This application incorporates large organic particles in the organic coating that are compressible. By dynamically adjusting the compressibility of these large particles, the wettability of the electrolyte can be modified: During battery assembly or charging / discharging, the large particles deform under pressure, temporarily increasing local porosity and promoting electrolyte wetting; after pressure release, partial rebound maintains structural stability, preventing a decrease in wettability due to pore collapse. If the compressibility d1 is too small, it results in low compressibility, leading to an excessively thick cell and low cell energy density; if the compressibility d1 is too large, it can cause pore blockage in the separator, affecting cell performance.

[0049] In some embodiments, the values ​​of the distance 'a' between the first organic particles, the distance 'b' between the first organic particles and the second organic particles, and the compressibility 'd' of the diaphragm in the first organic coating satisfy the following relationship: ; Where a is in μm and b is in μm. For example, It can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, or within the range of any two of the above values.

[0050] In some embodiments, the median particle size Dv50 of the first organic particles (large organic particles) is 3.8 to 11.0 μm. Exemplarily, it can be 3.8 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, or within any two of the above values.

[0051] In some embodiments, the particle size distribution width (SPAN = (Dv90 - Dv10) / Dv50) of the first organic particles (large organic particles) is 0.98 to 5.88. If the particle size distribution width is too wide, the particle size will not be concentrated, and the coating thickness will fluctuate greatly; if it is too narrow, the material cost will be too high.

[0052] In some embodiments, the median particle size Dv50 of the second organic particles (small particulate organic matter) is 0.3~0.8μm. For example, it can be 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, or within any two of the above values.

[0053] In some embodiments, the particle size distribution width (SPAN = (Dv90 - Dv10) / Dv50) of the second organic particles (small organic particles) is 1.56 to 4.17. If the particle size distribution width is too wide, the particle size will not be concentrated, and the coating thickness will fluctuate greatly; if it is too narrow, the material cost will be too high.

[0054] In some embodiments, the first organic particles (large organic particles) are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymers, but are not limited thereto.

[0055] In some embodiments, the first organic particles (small particulate organic matter) are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymers, but are not limited thereto.

[0056] In some embodiments, the polyvinylidene fluoride resin is obtained by copolymerizing ethane with another copolymerizable monomer (such as one or more of tetrafluoroethylene, hexafluoropropylene, trifluoroethylene, trichloroethylene, and fluoroethylene) or a mixture thereof.

[0057] In some embodiments, the areal density α and thickness β of the inorganic coating satisfy the relationship: 0.1 < α / β ≤ 5, where the unit of α is g / m³. 2 The unit of β is μm. Preferably, 0.7 ≤ α / β ≤ 3.75, more preferably, α / β = 3.5, or a range between the above values, exemplarily, can be: 0.1 < α / β ≤ 3.5, or 3.5 ≤ α / β ≤ 5. This application sets the areal density α (g / m³) of the inorganic coating. 2 The ratio α / β of the thickness β (μm) should be between 0.1 and 5. If the α / β ratio is too small, the coating adhesion is insufficient, affecting the thermal shrinkage of the separator; if the α / β ratio is too large, the coating particle packing density is too high, increasing the lithium-ion transport path and slowing lithium-ion wetting and diffusion. A α / β ratio between 0.1 and 5 provides the separator with good resistance to thermal shrinkage.

[0058] In some embodiments, the areal density α of the inorganic coating ranges from 0.5 to 4.2 g / m³. 2 .

[0059] In some embodiments, the thickness β of the inorganic coating ranges from 0.2 to 2.5 μm.

[0060] Figure 1 This is one schematic diagram of the diaphragm provided in this application. As shown, the diaphragm includes a base membrane 1 and a composite coating 2. The composite coating 2 includes a first organic coating 4 and an inorganic coating 5, forming a stacked structure of base membrane-inorganic coating-organic coating. The first organic coating 4 is coated with a mixture of first organic particles (large organic particles) 4.1 and second organic particles (small organic particles) 4.2. The mixing of large and small particles forms a gradient pore structure—large particles form macroscopic pores, while small particles fill microscopic gaps. This structure ensures rapid electrolyte penetration (through the pores of large particles) and increases capillary action through the small particles, promoting uniform distribution of the electrolyte within the diaphragm, thereby reducing interfacial impedance.

[0061] In some embodiments, the thickness D1 of the first organic coating ranges from 2.0 to 6.5 μm. For example, it can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 6.5 μm, or within any two of the above values.

[0062] In some embodiments, the thickness β of the inorganic coating ranges from 0.2 to 2.5 μm. For example, it can be 0.2 μm, 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, or within any two of the above values.

[0063] In some embodiments, the inorganic coating includes inorganic particles, but is not limited thereto.

[0064] In some embodiments, the particle size D of the inorganic particles 99 >D 90 >D 75 >D 50 >D 25 >D 10。

[0065] In some embodiments, the inorganic particles are selected from at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, silicon hydroxide, barium sulfate, zirconium oxide, calcium oxide, titanium dioxide, cerium dioxide, or apatite, but are not limited thereto.

[0066] In some embodiments, the median particle size Dv50 of the inorganic particles is 0.3 to 0.7 μm. For example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or within any two of the above values.

[0067] In some embodiments, the particle size distribution width SPAN (Dv90-Dv10) / Dv50) of the inorganic particles is 2.8 to 6.5.

[0068] In some embodiments, the specific surface area of ​​the inorganic particles is 8-16 m². 2 / g.

[0069] In some embodiments, the inorganic particles may be square, flake-shaped, spherical, etc., and may be regular or irregular in shape, but are not limited thereto.

[0070] In some embodiments, the first organic coating and / or inorganic coating further includes an adhesive.

[0071] In some embodiments, the first organic coating and / or inorganic coating is applied by one or more of the following methods: gravure coating, extrusion coating, dip coating, spray coating, dot coating, or wire bar coating.

[0072] In some embodiments, the adhesive is selected from one or more copolymers or mixtures of polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene (PTFE), polyhexafluoropropylene, and polytrifluoroethylene, but is not limited thereto.

[0073] In some embodiments, the composite coating is disposed on one side of the base film.

[0074] In some embodiments, the diaphragm further includes a second organic coating disposed on the surface of the base membrane away from the composite coating.

[0075] In some embodiments, a composite coating is disposed on one side of the base membrane, and the diaphragm further includes a second organic coating disposed on the surface of the base membrane away from the composite coating, the second organic coating comprising third organic particles.

[0076] Figure 2 Another schematic diagram of the diaphragm provided in this application is shown. As illustrated, the diaphragm includes a base membrane 1, a composite coating 2, and a second organic coating 3. The composite coating 2 includes a first organic coating 4 and an inorganic coating 5, forming a stacked structure of organic coating-base membrane-inorganic coating-organic coating. Specifically, an inorganic coating 2 is coated on one side of the base membrane 1, then the second organic coating 3 is coated on the opposite side of the inorganic coating 2, and finally the first organic coating 4 is coated on the same side of the inorganic coating.

[0077] In some embodiments, the thickness D2 of the second organic coating ranges from 0.3 to 1.0 μm. Exemplarily, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, or within any two of the above values.

[0078] In some embodiments, the second organic coating includes third organic particles.

[0079] In some embodiments, the distance f between the third organic particles satisfies the following condition: 0 ≤ f < 10 μm, and the percentage of f = 0 is < 100%. For example, f can be 0 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or within any two of the above values. If f is too small, the particles will accumulate too high, resulting in excessive adhesion between the particles and hindering electrolyte transport; if f is too large, capillary action will be weak, reducing the adhesion between the diaphragm and the electrode.

[0080] In some embodiments, the third organic particle is selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer; but is not limited thereto.

[0081] In some embodiments, the third organic particle is selected from PMMA.

[0082] In some embodiments, the median particle size Dv50 of the third organic particles is 0.3 to 0.8 μm. For example, it can be 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or within any two of the above values.

[0083] In some embodiments, the particle size distribution width of the third organic particles is 1.56 to 4.17.

[0084] In some embodiments, the base film includes at least one of PE base film or PE ceramic film, PP base film or PP ceramic film, PE / PP / PE composite base film or PE / PP / PE composite ceramic film, but is not limited thereto.

[0085] In some embodiments, the melting point of the base film is 80~150°C.

[0086] In some embodiments, the thickness of the base film is 2~10 μm.

[0087] In some implementations, the porosity of the base membrane is >30%.

[0088] In some embodiments, the air permeability of the base membrane is 50~200 sec / 100cc.

[0089] In some embodiments, the ceramic coating of the base film is a conventional 0.5~2μm ceramic coating.

[0090] <Battery Cell> A second aspect of this application also provides a battery cell comprising a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the separator being the aforementioned separator.

[0091] Since the battery cell adopts all the technical solutions of the separator in the above embodiments, it has at least all the beneficial effects brought about by the technical solutions in the above embodiments. That is, the battery cell adopts the above separator, and through multi-scale pore construction and dynamic adjustment of compressibility, it achieves synergistic optimization of electrolyte wettability and cycle stability, thereby improving the high cycle stability of the battery.

[0092] In some embodiments, the positive electrode sheet may include a positive current collector and a positive active material layer disposed on at least one side of the positive current collector.

[0093] In some embodiments, the positive current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is an aluminum foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.

[0094] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.

[0095] In some embodiments, the positive electrode active material layer may include a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.

[0096] In some embodiments, the positive electrode active material is selected from LiCoO2, LiNiO2, LiNixMnyO2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z The group consisting of O2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, Li2MnO3, LiFeO2, LiFePO4, LiMnPO4, and combinations thereof, wherein each x is independently 0.2 to 0.9; each y is independently 0.1 to 0.45; and each z is independently 0 to 0.2. The positive electrode active material of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as positive electrode active materials.

[0097] In some embodiments, the positive electrode active material is selected from LiCoO2, LiNiO2, and LiNi x Mn y O2, Li 1+ z Ni x Mn y Co 1-x-y O2, LiNi x Co y Al z The group consisting of O2, LiV2O5, LiTiS2, LiMoS2, LiMnO2, LiCrO2, LiMn2O4, LiFeO2, LiFePO4 and combinations thereof, wherein each x is independently 0.4 to 0.6; each y is independently 0.2 to 0.4; and each z is independently 0 to 0.1.

[0098] In some embodiments, the positive electrode active material is Li1+xNiaMnbCocAl(1-abc)O2; wherein -0.2≤x≤0.2, 0≤a<1, 0≤b<1, 0≤c<1 and a+b+c≤1.

[0099] In some embodiments, the positive electrode active material has the general formula Li 1+x Ni a Mn b Co c Al (1-a-b-c) O2, where 0.33≤a≤0.92, 0.33≤a≤0.9, 0.33≤a≤0.8, 0.5≤a≤0.92, 0.5≤a≤0.9, 0.5≤a≤0.8, 0.6≤a≤0.92 or 0.6≤a≤0.9; 0≤b≤0.5, 0≤b≤0.3, 0.1≤b≤0.5, 0.1≤b≤0.4, 0.1≤b≤0.3, 0.1≤b≤0.2 or 0.2≤b≤0.5; 0≤c≤0.5, 0≤c≤0.3, 0.1≤c≤0.5, 0.1≤c≤0.4, 0.1≤c≤0.3, 0.1≤c≤0.2 or 0.2≤c≤0.5.

[0100] In some embodiments, the positive electrode active material is doped with a dopant selected from the group consisting of Fe, Ni, Mn, Al, Mg, Zn, Ti, La, Ce, Sn, Zr, Ru, Si, Ge, and combinations thereof. In some embodiments, the dopant is not Fe, Ni, Mn, Mg, Zn, Ti, La, Ce, Ru, Si, or Ge. In some embodiments, the dopant is not Al, Sn, or Zr.

[0101] In some embodiments, the positive electrode active material may include LiNi. 0.33 Mn 0.33 Co 0.33 O2, LiNiO2, LiNi 0.4 Mn 0.4 Co 0.2 O2, LiNi 0.5 Mn 0.3 Co 0.2 O2, LiNi 0.6 Mn 0.2 Co 0.2 O2, LiNi 0.7 Mn 0.15 Co 0.15 O2, LiNi 0.8 Mn 0.1 Co 0.1 O2, LiNi 0.92 Mn 0.04 Co 0.04 O2, LiNi 0.8 Co 0.15 Al 0.05 At least one of O2.

[0102] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride (PVDF), poly(vinylidene fluoride)-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, fluorinated acrylate resin, polyacrylic acid, polyacrylonitrile, polyimide, polyurethane, polyvinyl butyral, polyvinylpyrrolidone (PVP), acrylic acid-acrylonitrile-acrylamide copolymer, and acrylic acid-acrylonitrile-acrylate copolymer. The positive electrode binder of this application is not limited to the above materials, but also includes other materials that can be used as battery positive electrode binders.

[0103] In some embodiments, the positive electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The positive electrode conductive agent in this application is not limited to the above materials, but also includes other materials that can be used as positive electrode conductive agents in batteries.

[0104] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector.

[0105] In some embodiments, the negative current collector is a metal foil or a composite current collector. In some embodiments, the metal foil is a copper foil. The composite current collector may include a metal foil substrate and a conductive layer disposed on at least one side of the metal foil substrate.

[0106] In some embodiments, the conductive layer may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, carbon fiber, carbon nanofiber, graphitized carbon sheet, carbon tube, carbon nanotube, activated carbon, and mesoporous carbon.

[0107] In some embodiments, the negative electrode active material may include natural graphite particles, synthetic graphite particles, hard carbon, soft carbon, mesophase carbon microspheres (MCMB), Sn, SnO2, SnO, Li4Ti5O 12 The negative electrode active material is selected from at least one of LTO, Si materials, silicon-carbon (Si-C) composite materials, silicon-nitrogen (Si-N) composite materials, and silicon-oxygen (Si-O) composite materials. The negative electrode active material of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as negative electrode active materials for batteries.

[0108] In some embodiments, the negative electrode binder may include at least one of polyacrylic acid, polymethacrylic acid, polyacrylate, polymethacrylate, polyacrylamide, styrene-butadiene rubber, acrylic styrene-butadiene rubber, acrylic acid-acrylonitrile-acrylamide copolymer, acrylic acid-acrylonitrile-acrylate copolymer, acrylonitrile-butadiene rubber, nitrile rubber, acrylonitrile-styrene-butadiene copolymer, acryloyl rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyvinyl alcohol, polyvinyl acetate, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethyl cellulose, hydroxypropyl cellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl cellulose, carboxymethyl chitosan, polyester, polyamide, polyether, polyimide, polycarboxylic acid ester, polycarboxylic acid, polyurethane, alginate, fluorinated polymer, chlorinated polymer, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropylene. The negative electrode binder of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode binders.

[0109] In some embodiments, the negative electrode conductive agent may include at least one of carbon, carbon black, graphite, expanded graphite, graphene, graphene nanosheets, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon fibers, carbon nanofibers, graphitized carbon sheets, carbon nanotubes, carbon nanotubes, activated carbon, and mesoporous carbon. The negative electrode conductive agent of this application is not limited to the above-mentioned materials, but also includes other materials that can be used as battery negative electrode conductive agents.

[0110] <Electrochemical Device> A third aspect of this application also proposes an electrochemical device comprising the aforementioned battery cell.

[0111] The electrochemical device provided in this application includes any device in which an electrochemical reaction occurs to convert chemical energy into electrical energy and vice versa. Specific, non-limiting examples include all types of primary batteries, secondary batteries, fuel cells, solar cells, or capacitors. In particular, the electrochemical device is a lithium secondary battery, including lithium metal secondary batteries, lithium-ion secondary batteries, lithium polymer secondary batteries, or lithium-ion polymer secondary batteries.

[0112] In some implementations, the electrochemical device includes a lithium-ion battery.

[0113] In some embodiments, the electrochemical device includes a positive electrode, a negative electrode, an electrolyte, and a separator, the separator being located between the positive and negative electrodes, and the separator used in the electrochemical device is the separator described above in this application.

[0114] In some embodiments, the electrolyte may include at least one of a gel electrolyte, a solid electrolyte, and a liquid electrolyte.

[0115] In some embodiments, the liquid electrolyte may include a non-aqueous solvent and a lithium salt.

[0116] In some embodiments, the lithium salt may include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate.

[0117] In some embodiments, the non-aqueous solvent may be at least one of carbonate compounds, carboxylic acid ester compounds, and ether compounds.

[0118] In some embodiments, the carbonate compound may include at least one of chain carbonate compounds, cyclic carbonate compounds, and fluorocarbonate compounds.

[0119] In some embodiments, the chain carbonate compound may include diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), and combinations thereof.

[0120] In some embodiments, the cyclic carbonate compound may include ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), vinyl ethylene carbonate (VEC), and combinations thereof.

[0121] In some embodiments, the fluorocarbonate compound may include at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate.

[0122] In some embodiments, the carboxylic acid ester compound may include at least one of methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid lactone, valerate lactone, mevalonate lactone, caprolactone, and methyl formate.

[0123] In some embodiments, the ether compound may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, and combinations thereof.

[0124] In some embodiments, the non-aqueous solvent may also include at least one of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate esters.

[0125] <Electronic Devices> In a fourth aspect, the present invention provides an electronic device comprising the electrochemical device described above.

[0126] The electronic device described in this application is not particularly limited and may be any electronic device known in the prior art.

[0127] The application of the electrochemical device in this application is not particularly limited, and it can be used in any electronic device known in the prior art. Some embodiments of this application include electronic devices such as mobile phones, smartphones, laptops, tablets, wearable devices, smartwatches, smart bracelets, smart glasses, power banks, televisions, game consoles, game controllers, digital cameras, smart speakers, headphones, keyboards, mice, monitors, drones, audio equipment, home appliances, toys, power tools, automobiles, motorcycles, electric bicycles, bicycles, robots, robot dogs, industrial robots, and android robots.

[0128] Unless otherwise specified in the following examples, the techniques or conditions described in the literature in this field or in accordance with the product instructions shall apply. All reagents or instruments without a specified manufacturer are commercially available conventional products.

[0129] Example 1 A lithium-ion battery, the preparation method includes the following steps: 1. Preparation of the diaphragm 1) The preparation steps of the first organic coating are as follows: Take 85 parts by weight of deionized water, add 0.005 parts by weight of dispersant (polyether modified siloxane), and stir at 200 rpm for 30 min; then add 1.5 parts by weight of adhesive aid 1 (polyacrylate), and stir at 1000 rpm for 30 min; add 2.4 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 6.675 μm, Dv90: 13.723 μm, glass transition temperature 48℃), and stir at 2000 rpm for 30 min; then add 1.0 part by weight of adhesive aid 2 (PVA 17-88), and stir at 500 rpm for 30 min; finally, add 10.095 parts by weight of small-particle polymer (PMMA, Dv50: 0.538 μm, Dv90: 0.998 μm, glass transition temperature 50℃) to obtain the first organic coating slurry.

[0130] 2) The preparation steps of the second organic coating slurry are as follows: Take 39 parts by weight of deionized water, add 4.5 parts by weight of adhesive aid (PVA 17-88), and stir at 1000 rpm for 30 min; add 56.45 parts by weight of small particle polymer (PMMA, Dv50: 0.538 μm, Dv90: 0.998 μm, glass transition temperature 50℃), and stir at 1000 rpm for 30 min; finally add 0.05 parts by weight of dispersant (fatty alcohol polyoxyethylene ether), and stir at 1000 rpm for 30 min to obtain the second organic coating slurry.

[0131] 3) The preparation steps of the inorganic coating slurry are as follows: Take 70 parts by weight of deionized water, add 20 parts by weight of inorganic material (boehmite, Dv10=1.136μm, Dv50=0.352μm, Dv90=1.261μm), and stir at 2000 rpm for 60 min; add 1.0 parts by weight of adhesive aid 1 (PVA 17-88), and stir at 1000 rpm for 30 min; add 3.7 parts by weight of adhesive aid 2 (polyacrylate), and grind at 750 rpm for 30 min; add 4.5 parts by weight of adhesive aid 3 (sodium carboxymethyl cellulose), and stir at 1000 rpm for 30 min; finally, add 0.8 parts by weight of dispersant (ethoxyacetylene glycol) to obtain the inorganic coating slurry.

[0132] 4) Slurry coating: (1) The inorganic coating slurry was coated onto a polyethylene (PE) base film (porosity 38%, air permeability 145 sec / 100cc) by a micro-gravure roller, and then dried in an oven at 45℃. The inorganic coating thickness was 0.9μm, and semi-finished product 1 was obtained.

[0133] (2) The slurry of the first organic coating is applied to the inorganic coating of the semi-finished product 1 by a micro-gravure roller, and then dried in an oven at 45°C. The thickness of the first organic coating is 4.5μm, and the semi-finished product 2 is obtained.

[0134] (2) The slurry of the second organic coating is applied to the opposite side of the inorganic coating of the semi-finished product 2 by a micro-gravure roller, and then dried in an oven at 45°C. The thickness of the second organic coating is 0.6μm, and the finished film is obtained.

[0135] 5) Methods for setting, measuring, and characterizing interparticle spacing (a, b, c) The particle spacing (a, b, c) is achieved by controlling the solid content ratio in the slurry. The lower the solid content, the more free space the particles have during the drying process, and the larger the spacing between a, b, and c. With a moderate solid content, the particles are "frozen" in their current positions in the early stages of drying, resulting in more uniform dispersion (moderate distance). If the solid content is too high, the particles are prone to agglomeration during the drying process (close distance).

[0136] Methods for measuring and characterizing spacing parameters (a, b, c): (1) Sample preparation: Take the sample of the coating membrane to be tested and cut it into 1cm×1cm size.

[0137] (2) Image acquisition: The coating surface was observed using a scanning electron microscope (SEM) at 1000x magnification. At least 10 non-overlapping fields of view were randomly selected and photographed.

[0138] (3) Image analysis: ImageJ image analysis software was used to process the SEM photos.

[0139] ① Define particles: Distinguish between large and small particles based on their size.

[0140] ② Measurement distance (a): Measure the straight-line distance between the geometric center of any large particle and the geometric center of the nearest neighboring large particle, denoted as a. Record the range of a values ​​(within 100μm) and the percentage of a=0 (i.e., the two large particles are in direct contact) out of the total number of cases.

[0141] ③Measure distance (b): Measure the distance between the geometric center of any large particle and the geometric center of the nearest neighboring small particle, and denot it as b. Calculate the percentage of cases where b=0 (small particles adhere to the surface of large particles).

[0142] ④ Measure distance (c): Measure the distance between the geometric center of any small particle and the geometric center of its nearest neighbor, denoted as c. Calculate the percentage of particles with c=0.

[0143] 6) Setting compressibility (d) (1) Sample preparation: 80mm diaphragm sample preparation Take 8 layers of membranes stacked together, and measure the thickness of these 8 layers as T0. Test 5 points (2 points above the membrane, 1 point in the middle, and 2 points below the membrane).

[0144] (2) After hot pressing in the hot press for one hour (85℃, 1MPa), the thickness of the 8 diaphragms is measured as T1 by a thickness gauge. Five points are tested (two points above the diaphragm, one point in the middle, and two points below the diaphragm). The test points are the same positions in (1).

[0145] (3) Calculate d: .

[0146] 2. Preparation of negative electrode sheet The negative electrode material silicon-carbon composite, conductive agent acetylene black, binder styrene-butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC) were thoroughly mixed in a deionized water solvent system at a mass ratio of 96.4:1.2:1.7:0.7. The mixture was then coated onto Cu foil, dried, rolled, and slit to obtain the negative electrode sheet. The expansion rate S of the negative electrode sheet was 14.62%.

[0147] 3. Preparation of positive electrode sheet The positive electrode material lithium cobalt oxide, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) were thoroughly mixed in an N-methylpyrrolidone solvent system at a mass ratio of 97.8:1.3:0.9. The mixture was then coated onto an Al foil, dried, rolled, and slit to obtain the positive electrode sheet.

[0148] 4. Preparation of electrolyte A solution prepared by mixing lithium salt LiPF6 with a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): ethylene carbonate (VC) = 25:25:15:31:4, mass ratio) at a mass ratio of 8:92 is used as the electrolyte for lithium batteries.

[0149] 5. Preparation of lithium-ion batteries The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes for safety isolation, and then wound to form the electrode assembly. The electrode assembly is placed in a packaging shell, electrolyte is injected, and after vacuum sealing, settling, formation, and shaping processes, a lithium-ion battery is obtained.

[0150] Example 2 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 85.4 parts by weight of deionized water and 2.0 parts by weight of large-particle polymer.

[0151] The rest is the same as in Example 1, and will not be repeated here.

[0152] Example 3 The difference from Example 1 is that in this example, the large-particle polymer in the first organic coating formulation is an acrylate copolymer with Dv50: 5.262 μm, Dv90: 12.240 μm, and a glass transition temperature of 46°C.

[0153] The rest is the same as in Example 1, and will not be repeated here.

[0154] Example 4 The difference from Example 1 is that in this example, in the preparation of the first organic coating, 85.195 parts by weight of deionized water, 2.3 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 5.262μm, Dv90: 12.240μm, glass transition temperature 46°C), and 10 parts by weight of small-particle polymer are used.

[0155] The rest is the same as in Example 1, and will not be repeated here.

[0156] Example 5 The difference from Example 1 is that in this example, in the preparation of the first organic coating, 85.295 parts by weight of deionized water, 2.2 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 5.262μm, Dv90: 12.240μm, glass transition temperature 46°C), and 10 parts by weight of small-particle polymer are used.

[0157] The rest is the same as in Example 1, and will not be repeated here.

[0158] Example 6 The difference from Example 1 is that in this example, the first organic coating is prepared using 84.995 parts by weight of deionized water, 2.0 parts by weight of large-particle polymer, and 10.5 parts by weight of small-particle polymer (PMMA, Dv50: 0.633 μm, Dv90: 1.056 μm, melting point 54°C). The rest is the same as in Example 1 and will not be repeated.

[0159] Example 7 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 85.6 parts by weight of deionized water, 1.8 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 7.814μm, Dv90: 16.886μm, glass transition temperature 63℃), and 10.095 parts by weight of small-particle polymer.

[0160] The rest is the same as in Example 1, and will not be repeated here.

[0161] Example 8 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 85.195 parts by weight of deionized water, 2.0 parts by weight of large-particle polymer, and 10.3 parts by weight of small-particle polymer (PMMA, Dv50: 0.617μm, Dv90: 1.029μm, glass transition temperature 48°C).

[0162] The rest is the same as in Example 1, and will not be repeated here.

[0163] Example 9 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 84.495 parts by weight of deionized water, 2.0 parts by weight of large-particle polymer, and 11 parts by weight of small-particle polymer (PMMA, Dv50: 0.617μm, Dv90: 1.029μm, glass transition temperature 48°C).

[0164] The rest is the same as in Example 1, and will not be repeated here.

[0165] Example 10 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 85.095 parts by weight of deionized water, 2.4 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 5.262 μm, Dv90: 12.24 μm, glass transition temperature 46°C), and 10 parts by weight of small-particle polymer (PMMA, Dv50: 0.633 μm, Dv90: 1.056 μm, glass transition temperature 54°C).

[0166] The rest is the same as in Example 1, and will not be repeated here.

[0167] Example 11 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 85.395 parts by weight of deionized water, 2.1 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 5.262 μm, Dv90: 12.24 μm, glass transition temperature 46°C), and 10 parts by weight of small-particle polymer (PMMA, Dv50: 0.538 μm, Dv90: 0.998 μm, glass transition temperature 50°C).

[0168] The rest is the same as in Example 1, and will not be repeated here.

[0169] Example 12 The difference from Example 1 is that in this example, the first organic coating is prepared by taking 82.995 parts by weight of deionized water, 1.5 parts by weight of large-particle polymer (acrylate copolymer, Dv50: 6.675 μm, Dv90: 13.723 μm, glass transition temperature 48°C), and 13 parts by weight of small-particle polymer (PMMA, Dv50: 0.617 μm, Dv90: 1.029 μm, glass transition temperature 48°C).

[0170] The rest is the same as in Example 1, and will not be repeated here.

[0171] Comparative Example 1 The difference from Example 1 is that in the preparation of the first organic coating: 87.495 parts by weight of deionized water, 5 parts by weight of large-particle polymer, and 5.0 parts by weight of small-particle polymer are used.

[0172] The rest is the same as in Example 1, and will not be repeated here.

[0173] Comparative Example 2 The difference from Example 1 is that in this comparative example, the first organic coating was prepared by taking 86.9 parts by weight of deionized water and 0.5 parts by weight of large-particle polymer.

[0174] The rest is the same as in Example 1, and will not be repeated here.

[0175] Comparative Example 3 The difference from Example 1 is that in this comparative example, the first organic coating is prepared by taking 86.895 parts by weight of deionized water, 4.8 parts by weight of large-particle polymer, and 5.8 parts by weight of small-particle polymer.

[0176] The rest is the same as in Example 1, and will not be repeated here.

[0177] Comparative Example 4 The difference from Example 1 is that in this comparative example, the first organic coating is prepared by taking 94.095 parts by weight of deionized water and 1.0 part by weight of small particle polymer.

[0178] The rest is the same as in Example 1, and will not be repeated here.

[0179] Comparative Example 5 The difference from Example 1 is that in this comparative example, the first organic coating is prepared by taking 77.095 parts by weight of deionized water and 18 parts by weight of small particle polymer.

[0180] The rest is the same as in Example 1, and will not be repeated here.

[0181] Comparative Example 6 The difference from Example 1 is that in this comparative example, the first organic coating is prepared by taking 95.495 parts by weight of deionized water, 1.0 part by weight of large-particle polymer, and 1.0 part by weight of small-particle polymer.

[0182] The rest is the same as in Example 1, and will not be repeated here.

[0183] Comparative Example 7 The difference from Example 1 is that in this comparative example, the large-particle polymer is polystyrene (Dv50: 5.289 μm, Dv90: 11.91 μm, glass transition temperature 136 °C).

[0184] The rest is the same as in Example 1, and will not be repeated here.

[0185] Comparative Example 8 The difference from Example 1 is that in this comparative example, the large-particle polymer is a low-crosslinked ultra-soft polyacrylate (Dv50: 4.105μm, Dv90: 8.398μm, glass transition temperature -20°C).

[0186] The rest is the same as in Example 1, and will not be repeated here.

[0187] Comparative Example 9 The difference from Example 1 is that in this comparative example, in the preparation of the second coating slurry: 30 parts by weight of deionized water were taken and 65.45 parts by weight of small particle polymer were added.

[0188] The rest is the same as in Example 1, and will not be repeated here.

[0189] Comparative Example 10 The difference from Example 1 is that in this comparative example, in the preparation of the second coating slurry: 75.45 parts by weight of deionized water were taken and 20 parts by weight of small particle polymer were added.

[0190] The rest is the same as in Example 1, and will not be repeated here.

[0191] Comparative Example 11 The difference from Example 1 is that in this comparative example, in the preparation of the inorganic coating slurry: 89 parts by weight of deionized water were taken and 1.0 part by weight of inorganic matter was added to it.

[0192] The rest is the same as in Example 1, and will not be repeated here.

[0193] Comparative Example 12 The difference from Example 1 is that in this comparative example, in the preparation of the inorganic coating slurry: 40 parts by weight of deionized water were taken and 50 parts by weight of inorganic matter were added to it.

[0194] The rest is the same as in Example 1, and will not be repeated here.

[0195] The parameter settings for Examples 1-12 and Comparative Examples 1-12 are shown in Table 1:

[0196] Test case 1. Coating thickness test: Separator (coating and base film together) thickness - base film thickness, the thickness is tested directly using a Maer thickness gauge; 2. Electrolyte wettability test method The horizontal diffusion method was used: the finished diaphragm was cut into 5mm wide strips and fixed on the fixture. 10μL of electrolyte was dropped onto the upper surface of the diaphragm with a pipette, and the diffusion length of the electrolyte was measured after 1 minute.

[0197] The testing steps are as follows: (1) Cut a 5mm diaphragm and fix both ends of the diaphragm to the two sides of the pull box with high temperature glue. The diaphragm is perpendicular to the side of the pull box. A steel ruler with a graduation of 0.5mm is placed parallel to one side of the diaphragm and kept parallel to the diaphragm. (2) Use a pipette to drop 10 μL of electrolyte onto the upper surface of the diaphragm; (3) Use a timer to measure for 1 minute. After 1 minute, subtract the corresponding readings on both sides of the droplet diffusion length on the ruler to obtain the length value of the electrolyte wettability test.

[0198] 3. Heat shrinkage test (1) Cut the diaphragm sample into 100mm×100mm pieces.

[0199] (2) Mark two mutually perpendicular reference lines (MD-longitudinal / TD-transverse) on the sample for measuring shrinkage.

[0200] (3) Initial size measurement: The initial length (L0) of the marking line is accurately measured with an optical measuring instrument to an accuracy of 0.1 mm.

[0201] (4) Heat treatment: Place the sample in an oven preheated to 130±2℃ and keep it for 0.5 hours.

[0202] (5) Measurement of dimensions after shrinkage Measure the length of the marked line (L1) after heating and calculate the thermal shrinkage rate. Heat shrinkage rate (%) = , The thermal shrinkage of MD (longitudinal) and TD (transverse) was calculated.

[0203] 4. Adhesion test (1) Cut the diaphragm into 30 mm pieces. 70mm, electrode cut into 30mm pieces 50mm; (2) Set the gauge pressure of the hot press to 3MPa, the temperature to 92℃, and the hot pressing time to 3min; (3) After hot pressing, take out the sample to test the adhesion. The peel width is 30mm and the peel speed is 100mm / min.

[0204] 5. Cyclic capacity test (1) Cell resting time: 10 min; (2) Discharge at a constant current of 1.0C, with a cutoff voltage of 3.5V; (3) Discharge at a constant current of 0.5C, with a cutoff voltage of 3.0V; (4) Let it sit: 10 minutes; (5) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (6) Charge at a constant current and constant voltage of 0.7C to 4.40V, with a cutoff rate of 0.05C; (7) Let it sit: 10 minutes; (8) Discharge at a constant current of 0.2C, with a cutoff voltage of 3.0V; (9) Let it sit: 10 minutes; (10) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (11) Charge to 4.40V at a constant current and constant voltage of 0.7C, with a cutoff rate of 0.05C; (12) Let it sit: 10 minutes; (13) Discharge at a constant current of 1.0C, with a cutoff voltage of 3.0V; (14) Shelving: 10 minutes; (15) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (16) Charge at a constant current and constant voltage of 0.7C to 4.40V, with a cutoff rate of 0.05C; (17) Shelving: 10 minutes; (18) Discharge at a constant current of 1.0C, with a cutoff voltage of 3.0V; (19) Shelving: 10 minutes; (20) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (21) Charge to 4.40V at a constant current and constant voltage of 0.7C, with a cutoff rate of 0.05C; (22) Shelving: 10 minutes; (23) Discharge at a constant current of 0.5C, with a cutoff voltage of 3.0V; (24) Shelving: 10 minutes; (25) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (26) Charge to 4.40V at a constant current and constant voltage of 0.7C, with a cutoff rate of 0.05C; (27) Shelving: 10 minutes; (28) Discharge at a constant current of 0.2C, with a cutoff voltage of 3.0V; (29) Shelving: 10 minutes; (30) Charge at a constant current and constant voltage of 1.2C to 4.20V, with a cutoff rate of 0.7C; (31) Charge to 4.40V at a constant current and constant voltage of 0.7C, with a cutoff rate of 0.05C; (32) Shelving: 10 minutes; (33) Discharge at a constant current of 1.0C, with a cutoff voltage of 3.5V; (34) Discharge at a constant current of 0.5C, with a cutoff voltage of 3.0V; (35) Shelving: 10 minutes; (36) Repeat steps 30-35 above.

[0205] The test results of Examples 1-12 and Comparative Examples 1-12 are shown in Table 2 below: Table 2

[0206] The results above show that, by comparing Examples 1-12, changes in spacing a, b, and c affect the compressibility d of the separator. a, b, and c together ensure good electrolyte wetting and adhesion of the separator, allowing the coating to maintain its designed microchannels even under pressure, thereby improving the cell's capacity retention. Simultaneously, changes in α and β affect the α / β ratio of the inorganic coating, ensuring good heat shrinkage resistance of the separator. All examples maintained a high level of 92.61%~95.62%, while all comparative examples decreased to 85.10%~91.62%. The multi-parameter synergistic effect is the core technical feature of this application: the inorganic coating provides a thermal stability framework, the first organic coating provides compression buffering and electrolyte storage functions, and the second organic coating provides interfacial bonding transition functions. The synergistic effect of these three layers enables the separator to simultaneously achieve excellent heat shrinkage inhibition, high wettability, and ultra-long cycle life. Even with significant differences in parameter values ​​(e.g., α ranging from 3 μm to 50 μm, and α / β ranging from 0.71 to 3.56), all 12 embodiments achieved significantly better overall performance than the comparative examples, demonstrating that the technical solution of this application has broad process adaptability and is beneficial for industrial production.

[0207] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A diaphragm, comprising a base membrane and a composite coating disposed on at least one side of the base membrane, characterized in that, The composite coating includes an inorganic coating and a first organic coating, wherein the first organic coating is disposed on the side of the inorganic coating away from the base film; The first organic coating comprises first organic particles and second organic particles, wherein the median particle size Dv50 of the first organic particles is greater than the median particle size Dv50 of the second organic particles; the inorganic coating comprises inorganic particles. In the first organic coating, the values ​​of the distance 'a' between the first organic particles, the distance 'b' between the first organic particles and the second organic particles, and the compressibility 'd' of the diaphragm satisfy the following relationship: ; Where a is in μm and b is in μm.

2. The diaphragm according to claim 1, characterized in that, The areal density α and thickness β of the inorganic coating satisfy the following relationship: 0.1 < α / β ≤ 5, where the unit of α is g / m³. 2 The unit of β is μm.

3. The diaphragm according to claim 1, characterized in that, The distance 'a' between the first organic particles satisfies the following condition: 0 ≤ a < 50 μm, and the percentage of a = 0 is < 50%.

4. The diaphragm according to claim 1, characterized in that, The distance b between the first organic particle and the second organic particle satisfies: 0 ≤ b < 25 μm, and the proportion of b = 0 is < 70%.

5. The diaphragm according to claim 1, characterized in that, The distance c between the second organic particle and the second organic particle satisfies: 0 ≤ c < 10 μm, and the proportion of c = 0 is < 90%.

6. The diaphragm according to claim 1, characterized in that, The median particle size Dv50 of the first organic particles is 3.8~11.0 μm, and the particle size distribution width is 0.98~5.

88. And / or, the median particle size Dv50 of the second organic particles is 0.3~0.8μm, and the particle size distribution width is 1.56~4.17; And / or, the median particle size Dv50 of the inorganic particles is 0.3~0.7μm, the particle size distribution width is 2.8~6.5, and the specific surface area is 8~16m². 2 / g.

7. The diaphragm according to any one of claims 1-6, characterized in that, Includes at least one of the following: (a1) The first organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (a2) The second organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (a3) The inorganic particles are selected from at least one of alumina, boehmite, magnesium hydroxide, silicon dioxide, silicon hydroxide, barium sulfate, zirconium oxide, calcium oxide, titanium dioxide, cerium dioxide, or apatite; (a4) The thickness D1 of the first organic coating ranges from 2.0 to 6.5 μm; (a5) The thickness β of the inorganic coating ranges from 0.2 to 2.5 μm; (a6) The compressibility d of the diaphragm satisfies: 0 < d < 100%.

8. The diaphragm according to claim 1, characterized in that, The composite coating is disposed on one side of the base membrane, and the diaphragm further includes a second organic coating, which is disposed on the surface of the base membrane away from the composite coating, and the second organic coating includes third organic particles.

9. The diaphragm according to claim 8, characterized in that, Includes at least one of the following: (b1) The thickness D2 of the second organic coating ranges from 0.3 to 1.0 μm; (b2) The distance f between the third organic particles satisfies: 0 ≤ f < 10 μm, and the percentage of f = 0 is < 100%; (b3) The third organic particles are selected from at least one of polyvinylidene fluoride or polyvinylidene fluoride resin, polyamide, polyimide, polyacrylonitrile, polyethylene oxide, polyurethane, polyphenylene ether, polyethylene, polypropylene, polyetherimide, polyethylene terephthalate, polylactic acid, or acrylate copolymer. (b4) The median particle size Dv50 of the third organic particles is 0.3~0.8μm and the particle size distribution width is 1.56~4.

17.

10. A battery cell, characterized in that, It includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, wherein the separator is the separator according to any one of claims 1-9.

11. An electrochemical device, characterized in that, Including the battery cell as described in claim 10.

12. An electronic device comprising the electrochemical device as claimed in claim 11.